Making the design process in design education explicit: two exploratory case studies - Dooren, Elise van; Boshuizen, Els; Merriënboer, Jeroen van; Asselbergs, Thijs; Dorst, Machiel van (Design and Technology Education: An International Journal, 2020)
The aim of design education is that students learn to think and act like designers. However, the focus in the design studio is mainly on the design product, whereas the ‘why and how’ of the design process are barely addressed. A risk of learning by performing real-life tasks without addressing the skills involved, that is, without receiving appropriate support and guidance, is that learners are overwhelmed by the complexity of the tasks. To make the design process explicit, a conceptual framework is developed in earlier research. This paper reports a first evaluation how articulation of basic designerly1 skills with the help of a conceptual tool is perceived by students and teachers and whether it changes students’ conceptions of the design process and their self-efficacy. In two exploratory case studies, questionnaires give insight. The first is a short intervention in which student’s perception is measured. In the second case study the design process was addressed in the design studio. It measured changes in student’s conceptions and self-efficacy. Also, insight is provided in teacher’s perception of working with the framework. The results of these exploratory studies indicate a positive effect. The teachers involved perceived the framework as a structuring factor during the tutoring sessions, for both teacher and students. Students did perceive explanation of the design process as being helpful. A change in students’ design conceptions and an increase in self-efficacy is seen.